The Influence of Financial Literacy on Student Financial Management Behavior - Salsabila, Najla Hasna; Hadi, Tri Sabila; Tambunan, Nurma (Education Achievement: Journal of Science and Research, 2024)
This research aims to determine the influence of financial literacy on students' financial management behavior. This research is quantitative research, with samples taken using purposive sampling techniques. The population of this study were PGRI Indraprasta University students and the sample in this study was 30 students. The data collection method uses a questionnaire to measure each variable. Data were analyzed using descriptive statistics and inferential statistics. The results of descriptive analysis show an average financial literacy of 37.10 and student financial management behavior of 39.30. The results of the inferential analysis show that the calculated t value (2.832) is in the acceptance area so that the calculated t value is greater than the t table value (1.701). So it can be concluded that H1 is accepted, which means there is an influence between financial literacy on students' financial management behavior.